Silicon Application Modulates the Growth, Rhizosphere Soil Characteristics, and Bacterial Community Structure in Sugarcane - Deng, Quanqing; Yu, Taobing; Zeng, Zhen; Ashraf, Umair; Shi, Qihan; Huang, Suihua; Lian, Tengxiang; Chen, Jianwen; Muzaffar, Wardah; Shen, Wankuan (Frontiers in Plant Science, 2021)
Silicon (Si) deficiency, caused by acidic soil and rainy climate, is a major constraint for sugarcane production in southern China. Si application generally improves sugarcane growth, however, there are few studies of the relationships among enhanced plant growth, changes in rhizosphere soil, and bacterial communities. A field experiment was conducted to measure sugarcane agronomic traits, plant nutrient contents, rhizosphere soil enzyme activities and chemical properties and the rhizosphere bacterial community diversity and structure of three predominant sugarcane varieties under two Si treatments i.e., 0 and 200 kg SiO2 ha-1 regarded as Si0 and Si200, respectively. Results showed that Si application substantially improved the sugarcane stalk fresh weight, and Si, phosphorus (P), and potassium (K) contents comparing to Si0, and had an obvious impact on rhizosphere soil pH, available Si (ASi), available P (AP), available K (AK), total phosphorus (TP) and the activity of acid phosphatase. Furthermore, the relative abundances of Proteobacteria showed a remarkable increase in Si200, which may be dominant groups in sugarcane growth under Si application. Interestingly, the AP was noticed as a major factor that caused bacterial community structure differences between the two Si treatments according to canonical correspondence analysis (CCA). In addition, the association network analysis indicated that Si application enriched the rhizosphere bacterial network, which could be beneficial to sugarcane growth. Overall, appropriate Si application i.e., 200 kg SiO2 ha-1 promoted sugarcane growth, changed rhizosphere soil enzyme activities and chemical properties as well bacterial community structures.